2012
DOI: 10.1021/jm300618u
|View full text |Cite
|
Sign up to set email alerts
|

Indole-Derived Psammaplin A Analogues as Epigenetic Modulators with Multiple Inhibitory Activities

Abstract: A SAR study has been carried out around a modified scaffold of the natural product psammaplin A obtained by replacing the o-bromophenol unit by an indole ring. A series of indole psammaplin A constructs were generated in a short synthetic sequence that starts with the functionalization of the C3 indole position with in situ generated nitrosoacrylate, and this is followed by protection of the β-indole-α-oximinoesters, saponification, condensation with symmetrical diamines, and deprotection. Biochemical and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 126 publications
(248 reference statements)
1
31
0
Order By: Relevance
“…To bridge this experimental gap, we set out to establish the pharmacokinetics of one of the best evaluated non-nucleosidic DNMT inhibitors, RG 108 [17]. The data show that once-daily subcutaneous injections suffice to reach peak plasma concentrations above IC 50 and, in the presence of cytochrome P450 inhibition and multiple-dose administration, trough levels close to recently published IC 50 values or effective concentrations of 1-5 lM [21,23]. Although systematic phenotyping of the animals was not in the scope of this study, we observed no evident effects on the animals.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…To bridge this experimental gap, we set out to establish the pharmacokinetics of one of the best evaluated non-nucleosidic DNMT inhibitors, RG 108 [17]. The data show that once-daily subcutaneous injections suffice to reach peak plasma concentrations above IC 50 and, in the presence of cytochrome P450 inhibition and multiple-dose administration, trough levels close to recently published IC 50 values or effective concentrations of 1-5 lM [21,23]. Although systematic phenotyping of the animals was not in the scope of this study, we observed no evident effects on the animals.…”
Section: Discussionmentioning
confidence: 73%
“…Genistein inhibits DNMT1 at 50 lM [13] and published IC 50 values for RG 108 range from 115 nM [17] to much higher concentrations needed [18,19] up to a mere 20% inhibition at 100 lM [20]. Several reports now describe the IC 50 or effective concentration of RG 108 around 1-5 lM [21][22][23].…”
mentioning
confidence: 99%
“…In addition to the previously reported activity as a topoisomerase II inhibitor, this compound has been described as a new histone deacetylase and DNA methyltransferase inhibitor, epigenetic modifiers in the silencing of tumor supressor genes [118]. Because of their multi(epi)target features and their action in ex vivo samples, psammaplin A and its derivatives are attractive molecules for the modulation of epigenetic disorders [119,120]. Recent pharmacokinetics and tissue distribution studies indicate a preferential distribution of psammaplin A to lung, suggesting the potential of this compound as a lung cancer treatment agent [121].…”
Section: Compounds That Inhibit the Extracellular Matrix Remodellingmentioning
confidence: 99%
“…To test our hypothesis, we screened 12 modulators, some of which have single or multiple epigenetic targets. From these studies, we identified an indole derivative of psammaplin A (Psa_A) named UVI5008, known in the literature as a novel epigenetic modulator for cancer treatment 22 , which showed significant inhibitory activity against MRSA.…”
Section: Introductionmentioning
confidence: 99%